PENGARUH TRANSFORMATIONAL LEADERSHIP & COMPENSATION TERHADAP EMPLOYEE PERFORMANCE DIMEDIASI OLEH JOB SATISFACTION - Mohammad Eko Budiratmoko; Erny Tajib (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2022)
This study aims to analyze the effect of transformational leadership and compensation on employee performance mediated by job satisfaction variables. The job satisfaction variable here functions as a mediating variable that researchers want to prove that it has an impact on employee performance. A company has an important component, namely employees as a fundamental asset. If employees are satisfied with what the company has given them, it can affect the progress of the company because employees feel motivated to work. Things that can affect employee performance include the supervisor's factor leading the employees, and also the compensation factor given to employees. So that if the two components are fulfilled properly it will have an impact on increasing employee performance which of course brings benefits to the company. The sample companies in this study are PT. Waskita Karya (Persero) Tbk. The data collection method in this study used a question questionnaire which was distributed to employees to be filled out. Then the data obtained were analyzed by multiple regression analysis using SPSS software. The results showed that there was a positive effect of transformational leadership and compensation on employee performance mediated by job satisfaction. All hypotheses in this study are proven except for hypothesis number 4, namely transformational leadership has a negative effect on employee performance, due to the COVID-19 pandemic which affects the company's production decline from the target. However, if job satisfaction is included as a mediating variable, transformational leadership will have a positive impact on employee performance. From the results obtained, the leader must be able to teach his employees to be more creative at work and compensation must also be increased so that employee performance can increase